Between protest and policy: Women claim their right to agricultural land in rural China and India - Govind Kelkar (United Nations Research Institute for Social Development (UNRISD), 2016)
This research was conceptualized to ascertain the state response to women's extraprocedural claims making to land through collective and individual protests, demonstrations, public performances and women farmers' conclaves for building public opinion against the gender differential arrangements in land tenure and agrarian production system in India. An attempt was also made to understand China's policy on women's legal and equal rights to land since the 1950s. The author situates the discussion on women and land in the broader context of women's emerging agential power against the patriarchal forces of the state, market fundamentalism and social cultural norms that influence both formal and informal institutions at various levels. Women's claims are thus framed against two major related factors: an insidious state-backed development policy that keeps women dependent on the male as the head of the household; and a combination of institutional structures with social norms and legal rules that shut most rural women out of land and property ownership. [...] This study is divided into eight sections. The introduction outlines the conceptual framework and raises the major questions of the study. Section 2 discusses discriminatory social norms and attitudes. Section 3 describes the policy change in response to women's historical struggles for equality against the gender regimes in Asia, followed by women's right to land and inheritance in the two countries in section 4. Major drivers of policy change are discussed in section 5. Section 6 assesses change in the practice of women's lives. Some continued challenges related to the state's institutional structures and the market are discussed in section 7. The concluding section 8 suggests some desirable policy and action towards mitigating gendered negative outcomes of past agricultural development.
Additional information: Prepared for the UNRISD project on: When and Why Do States Respond to Women's Claims? Understanding Gender-Egalitarian Policy Change in Asia
Keywords: 330